Preparation process of multi-layer composite wood fireproof door
By using calcium-based composite materials and γ-alumina to form a calcium hexaaluminate ceramic network skeleton and a chemical expansion flame retardant system in wooden fire doors, the problems of easy powdering of the insulation layer and easy detachment of the char layer in wooden fire doors at high temperatures are solved, achieving the effects of high-efficiency heat insulation, structural stability and smoke suppression.
Patent Information
- Application Number
- CN202611215033.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-11-06
AI Technical Summary
Existing wooden fire doors are prone to shrinkage and powdering of the insulation layer under high temperatures, forming thermal bridges. The temperature of the unexposed side rises rapidly, and the organic adhesives decompose and release heat and toxic fumes during a fire. The intumescent flame-retardant coating has low carbon strength and is easy to fall off. The oxide phase generated at high ceramicization temperature has insufficient density, making it difficult to meet stringent fire protection requirements.
Amorphous nano-calcium carbonate is formed by combining calcium-based composite material with γ-alumina. Through high-temperature decomposition, calcium hexaaluminate ceramic network skeleton is generated. Combined with a chemical expansion flame retardant system of expanded graphite, pentaerythritol, melamine and ammonium tripolyphosphate, a dense carbon layer is formed. Calcium gluconate captures acidic gases. Inorganic nano-components are used to improve the coating uniformity, forming a multi-layer composite wood fire door.
It significantly improves the medium- and high-temperature insulation and integrity of fire doors, extends the fire resistance limit, suppresses smoke release, and enhances the structural stability and smoke suppression performance of fire doors.
Smart Images

Figure CN123040183A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of fire door flame retardant technology, and in particular relates to a manufacturing process of a multi-layer composite wood fire door. Background Technology
[0002] Wooden fire doors are widely used in the construction industry due to their advantages such as light weight, good decorative properties, and ease of processing. However, wood itself is flammable, and in order to achieve the specified fire resistance limit, wooden components usually need to be treated with flame retardants or have a heat-insulating and flame-retardant layer added inside.
[0003] Currently, common flame-retardant methods for wooden fire doors include impregnation with flame retardants, application of fire-resistant boards, and filling with inorganic materials such as rock wool or perlite. Among these, filled fire doors extend fire resistance by filling the interior of the door leaf with inorganic insulation materials. However, ordinary inorganic fillers (such as rock wool and perlite boards) are prone to shrinkage and pulverization at high temperatures, forming thermal bridges and causing the temperature of the unexposed surface to rise rapidly, making it difficult to meet more stringent fire protection requirements. Furthermore, to improve the integrity and strength of the insulation layer, adhesives are often used to bond it to the wooden frame. However, organic adhesives decompose and burn in a fire, releasing large amounts of heat and toxic fumes, which can actually exacerbate the fire.
[0004] Intumescent flame-retardant coatings are another common method, which mainly rely on acid sources, carbon sources, and gas sources to form an intumescent flame-retardant system, forming an intumescent char layer when heated. However, ordinary intumescent char layers have low strength, are easily eroded off by flames, and the char layer itself will oxidize and ablate at high temperatures, resulting in insufficient heat insulation durability.
[0005] In recent years, some studies have attempted to introduce ceramizable fillers into flame-retardant systems to enhance the char layer by forming a ceramic phase at high temperatures. For example, oxides are produced by the decomposition of aluminum hydroxide and magnesium hydroxide. However, these oxides have high ceramization temperatures and the resulting phases are not dense enough, thus limiting their ability to suppress flue gas.
[0006] Therefore, how to construct a multi-layer composite wood fire door that combines high-efficiency heat insulation, structural stability, and excellent smoke suppression performance is an urgent problem to be solved in this field. Summary of the Invention
[0007] To address the aforementioned issues, this application provides a manufacturing process for a multi-layer composite wood fireproof door.
[0008] This application provides a manufacturing process for a multi-layer composite wood fireproof door, comprising the following steps: Provide flame-retardant finish layers, spacers, and frame layers; Preparation of a heat-insulating and flame-retardant layer: The heat-insulating and flame-retardant layer includes a solid wood frame, a flame-retardant filler layer filled within the solid wood frame, and a flame-retardant coating applied to both sides of the heat-insulating and flame-retardant layer; the flame-retardant coating is formed by coating material through coating and curing, the coating material comprising calcium-based composite material, calcium gluconate, ammonium tripolyphosphate, epoxy resin, expanded graphite, pentaerythritol, melamine, and surfactant; the calcium-based composite material comprises nano-calcium carbonate base material and γ-alumina; The first decorative layer, the first spacer layer, the heat insulation and flame retardant layer, the frame layer, the second spacer layer, and the second decorative layer are stacked in that order and then cold-pressed to obtain the final product.
[0009] Furthermore, the coating material comprises, by weight, 12-18 parts of calcium-based composite material, 8-12 parts of calcium gluconate, 12-18 parts of ammonium tripolyphosphate, 35-45 parts of epoxy resin, 2-4 parts of expanded graphite, 8-12 parts of pentaerythritol, 5-8 parts of melamine, and 0.3-0.8 parts of hexadecyltrimethylammonium bromide.
[0010] Furthermore, the preparation method of the calcium-based composite material includes: 1) Add enzymatically hydrolyzed peptides to calcium chloride solution, mix well, then add potassium bicarbonate solution to carry out precipitation reaction. After the reaction is completed, adjust the pH to neutral, separate and dry to obtain nano calcium carbonate base material. 2) Mix the obtained nano-calcium carbonate base material with γ-alumina at a mass ratio of 1:5 to 7 to obtain calcium-based composite material.
[0011] Furthermore, in step 1), the enzymatically hydrolyzed polypeptide is an enzymatic hydrolysis product of collagen, with a molecular weight distribution range of 2000-5000 Da, and has a double helix structure formed by glycine-proline-hydroxyproline repeating sequences.
[0012] Furthermore, in step 2), the average particle size of the γ-alumina is 1–2 μm.
[0013] Furthermore, the flame-retardant filling layer is composed of perlite, rock wool, and silica aerogel mixed in a mass ratio of 1:0.4-0.6:0.2-0.4.
[0014] Furthermore, the decorative layer is a sliced catalpa veneer or ash veneer with a thickness of 0.3 to 0.8 mm, which is impregnated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624 B1.
[0015] Furthermore, the spacer layer is a three-layer plywood with a thickness of 3-8 mm, which is impregnated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624 B1.
[0016] Furthermore, the frame layer is a solid wood frame made of poplar or pine, with a thickness of 15-25mm, and is treated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624 B1.
[0017] Furthermore, the total thickness of the heat-insulating and flame-retardant layer is 40-50mm, wherein the thickness of the solid wood frame is flush with the thickness of the flame-retardant filling layer, and the total thickness of the flame-retardant coating is 2-4mm.
[0018] Furthermore, the flame-retardant filling layer is composed of perlite, rock wool, and silica aerogel mixed in a mass ratio of 1:0.4–0.6:0.2–0.4. The three materials form a gradient thermal insulation pore structure: perlite provides a coarse-porous skeleton, rock wool fibers provide interwoven reinforcement, and silica aerogel fills the micro- and nano-pores, producing a significant synergistic thermal insulation effect.
[0019] Compared with the prior art, this application has the following beneficial effects: This application utilizes the double helix structure of enzymatically hydrolyzed peptides as a template and control agent to induce the formation of amorphous nano-calcium carbonate particles. These amorphous nano-calcium carbonate particles possess extremely high specific surface area and reactivity. When combined with γ-alumina, in a high-temperature fire environment, the amorphous calcium carbonate decomposes, releasing carbon dioxide and diluting oxygen. Simultaneously, the calcium oxide component undergoes a low-temperature in-situ solid-phase reaction with γ-alumina, gradually generating lamellar calcium hexaaluminate crystals. Calcium hexaaluminate possesses a magnetolite-type layered structure, with its crystals interlocking and interpenetrating in lamellar form, constructing a dense ceramic network framework in situ within the expanded carbon layer. This significantly improves the high-temperature strength and erosion resistance of the carbon layer, effectively blocking heat and oxygen transfer, and significantly enhancing the insulation and integrity of fire doors at medium and high temperatures, thus extending their fire resistance limit.
[0020] Simultaneously, the chemically expanded flame-retardant system composed of expanded graphite, pentaerythritol, melamine, and ammonium tripolyphosphate forms an expanded char layer. Calcium gluconate decomposes at high temperatures to produce calcium oxide, which participates in the formation of calcium hexaaluminate and captures acidic gases produced by wood combustion, suppressing smoke. Hexadecyltrimethylammonium bromide acts as a surfactant, improving the dispersibility of inorganic nano-components in the epoxy resin matrix and enhancing the uniformity and adhesion of the coating. Furthermore, the chemically expanded components and ceramicized components in the flame-retardant coating work synergistically to form an expanded heat-insulating layer in the early stages of a fire and transform into a ceramic-reinforced char layer in the middle and later stages, achieving all-weather thermal protection. Attached Figure Description
[0021] Figure 1 The thermal conductivity test data are for the samples used in the embodiments and comparative examples of this application. Detailed Implementation
[0022] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0024] When using “including,” “having,” and “contains” as described herein, the intention is to cover non-exclusive inclusion, unless an explicit qualifying term such as “only,” “consisting of,” etc., is used, in which case another component may be added.
[0025] The terms "preferred," "more preferably," "better," and "even better" used in this application refer to embodiments of this application that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this application. That is, in this application, "preferred," "more preferably," "better," and "even better" are merely descriptions of implementations or embodiments with better effects, but do not constitute a limitation on the scope of protection of this application.
[0026] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0027] In this application, "at least one" means one or more, such as one, two, or more. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layered" means at least two layers, such as two layers, three layers, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.
[0028] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0029] Unless otherwise specified, all steps in this application may be performed sequentially or randomly. For example, the method comprising steps (a) and (b) indicates that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc. Unless otherwise stated, singular terms may include plural forms and should not be construed as having a quantity of one.
[0030] The present application will be further illustrated by the following examples, but these examples do not limit the scope of the present application.
[0031] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this application, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description in this application, any prior art methods, equipment, and materials similar to or equivalent to those described, used, or made by the methods, equipment, and materials in the embodiments of this application may be used to implement this application.
[0032] Example 1 The manufacturing process of the multi-layer composite wood fireproof door in this embodiment includes the following steps: The layers are stacked sequentially in the order of first decorative layer, first spacer layer, heat insulation and flame retardant layer, frame layer, second spacer layer, and second decorative layer; formaldehyde-free soybean protein adhesive is evenly applied between each layer at a coating amount of 120g / m². 2 Place it in a cold press and cold press it for 4 hours at room temperature and a unit pressure of 1.2 MPa. After depressurization, let it stand and cure for 72 hours to obtain a multi-layer composite wood fireproof door.
[0033] The veneer is made of sliced catalpa veneer, 0.5 mm thick, with a moisture content of less than 10%. The catalpa veneer is impregnated with phytic acid solution, and its flame retardant performance meets GB 8624-2012-B1 level.
[0034] The spacer layer is made of three layers of plywood, 0.5cm thick. The plywood is impregnated with phytic acid solution and its flame retardant performance reaches GB8624-2012-B1 level.
[0035] The heat insulation and flame retardant layer consists of a solid wood frame, a flame retardant filling layer inside the solid wood frame, and a flame retardant coating on both sides. The total thickness of the heat insulation and flame retardant layer is 43mm, the thickness of the solid wood frame is 40mm, and the total thickness of the flame retardant coating is 3mm.
[0036] The flame-retardant filler layer is composed of perlite, rock wool, and silica aerogel in a mass ratio of 1:0.5:0.3.
[0037] The flame-retardant coating is prepared by the following steps: 15 kg of calcium-based composite material, 10 kg of calcium gluconate, 15 kg of ammonium tripolyphosphate, 40 kg of epoxy resin E44, 3 kg of expanded graphite, 10 kg of pentaerythritol, 6.5 kg of melamine, and 0.5 kg of cetyltrimethylammonium bromide are mixed evenly to obtain the coating material, which is then evenly coated onto the flame-retardant filler layer and the surface of the solid wood frame. Multiple coatings are applied, and the coating is cured and dried.
[0038] Calcium-based composite materials are prepared using the following steps: 1) Add 15g of enzymatically hydrolyzed polypeptide to 1000mL of saturated calcium chloride solution and mix well to obtain the solution; add potassium bicarbonate solution with carbonate concentration of 3.5mmol / L to the calcium solution, adjust the pH to neutral after sufficient precipitation, filter and vacuum dry to obtain nano calcium carbonate base material; 2) Take nano-calcium carbonate base material and γ-alumina and mix them evenly at a mass ratio of 1:6.
[0039] The average particle size of alumina is 1.5 μm.
[0040] The frame layer is made of poplar wood, with dimensions of 200×150×20mm. The poplar wood frame is treated with phytic acid solution impregnation, and its flame retardant performance reaches GB 8624-2012-B1 level.
[0041] Example 2 The difference from Example 1 is that the mass ratio of perlite, rock wool, and silica aerogel in the flame-retardant filler layer is 1:0.6:0.4. In step (1) of the calcium-based composite material preparation, the calcium chloride concentration is 8 mmol / L, the potassium bicarbonate concentration is 4 mmol / L, and the amount of enzymatically hydrolyzed polypeptide added is 18 g. The average particle size of γ-alumina is 2 μm, and the mass ratio of the base material to γ-alumina is 1:7. The coating material formulation is: 12 kg of calcium-based composite material, 12 kg of calcium gluconate, 18 kg of ammonium tripolyphosphate, 45 kg of epoxy resin, 4 kg of expanded graphite, 12 kg of pentaerythritol, 8 kg of melamine, and 0.8 kg of hexadecyltrimethylammonium bromide. The rest is the same as in Example 1.
[0042] Example 3 The difference from Example 1 is that the flame-retardant filler layer ratio is 1:0.4:0.2. The coating formulation is: 18 kg calcium-based composite material, 8 kg calcium gluconate, 12 kg ammonium tripolyphosphate, 35 kg epoxy resin, 2 kg expanded graphite, 8 kg pentaerythritol, 5 kg melamine, and 0.3 kg hexadecyltrimethylammonium bromide. The cold pressing pressure is 1.0 MPa, and the time is 6 hours. The rest is the same as in Example 1.
[0043] Comparative Example 1 In the preparation of calcium-based composite material, no enzymatic hydrolysis of peptides was added. Instead, calcium chloride and potassium bicarbonate were reacted directly to generate calcium carbonate precipitate. Other steps were the same as in Example 1.
[0044] Comparative Example 2 In the preparation of the calcium-based composite material, only the amorphous nano-calcium carbonate base material prepared in step 1) of Example 1 is used, without mixing with γ-alumina. 15 kg of this base material is directly added to the coating material, and the rest is the same as in Example 1.
[0045] Comparative Example 3 Expanded graphite, pentaerythritol, and melamine were not added to the coating. To maintain the solid content, an equal mass of epoxy resin was added. The rest was the same as in Example 1.
[0046] Performance testing 1. Fire resistance test was conducted in accordance with GB / T 7633-2008 "Fire resistance test method for doors and roller shutters". The change of the average temperature of the unexposed surface with the fire exposure time was recorded to determine the fire resistance integrity and fire insulation performance. The comprehensive performance data are shown in Table 1.
[0047] 2. The thermal conductivity of each sample was tested using the hot-wire method at different temperatures, ranging from 200 to 800℃. The results are as follows: Figure 1 As shown.
[0048] Analysis of Table 1 shows that in Comparative Example 2, where ordinary calcium carbonate was used to replace the calcium-based composite material, an effective ceramic-reinforced structure could not be formed at high temperatures, the carbon layer was easily damaged and detached, and the refractory performance decreased by about 25%. Comparative Example 1 did not use enzymatic peptide regulation; the calcium carbonate was in its conventional crystalline form with low reactivity, resulting in a low amount of calcium hexaaluminate produced and a weakened carbon layer reinforcement effect.
[0049] analyze Figure 1 It can be seen that the thermal conductivity of all samples increases with increasing temperature, which is due to the enhanced radiative heat transfer at high temperatures. The sample in the example maintained a low level throughout the entire temperature range, indicating that its thermal insulation performance was stable. The thermal conductivity of Comparative Example 1 and Comparative Example 2 was higher than that of Example 1, especially above 500℃, indicating that the formation of the calcium hexaaluminate ceramic phase can effectively suppress thermal radiation conduction at high temperatures.
[0050] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A process for the preparation of a multi-layer composite wood fire door, characterized in that: Includes the following steps: Provide flame-retardant finish layers, spacers, and frame layers; Preparation of a heat-insulating and flame-retardant layer: The heat-insulating and flame-retardant layer includes a solid wood frame, a flame-retardant filler layer filled within the solid wood frame, and a flame-retardant coating applied to both sides of the heat-insulating and flame-retardant layer; the flame-retardant coating is formed by coating material through coating and curing, the coating material comprising calcium-based composite material, calcium gluconate, ammonium tripolyphosphate, epoxy resin, expanded graphite, pentaerythritol, melamine, and surfactant; the calcium-based composite material comprises nano-calcium carbonate base material and γ-alumina; The first decorative layer, the first spacer layer, the heat insulation and flame retardant layer, the frame layer, the second spacer layer, and the second decorative layer are stacked in that order and then cold-pressed to obtain the final product.
2. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The coating material comprises, by weight, 12-18 parts of calcium-based composite material, 8-12 parts of calcium gluconate, 12-18 parts of ammonium tripolyphosphate, 35-45 parts of epoxy resin, 2-4 parts of expanded graphite, 8-12 parts of pentaerythritol, 5-8 parts of melamine, and 0.3-0.8 parts of hexadecyltrimethylammonium bromide.
3. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The preparation method of the calcium-based composite material includes: 1) Add enzymatically hydrolyzed peptides to calcium chloride solution, mix well, then add potassium bicarbonate solution to carry out precipitation reaction. After the reaction is completed, adjust the pH to neutral, separate and dry to obtain nano calcium carbonate base material. 2) Mix the obtained nano-calcium carbonate base material with γ-alumina at a mass ratio of 1:5 to 7 to obtain calcium-based composite material.
4. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: In step 1), the enzymatically hydrolyzed polypeptide is an enzymatic hydrolysis product of collagen, with a molecular weight distribution range of 2000-5000 Da, and has a double helix structure formed by glycine-proline-hydroxyproline repeating sequences.
5. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: In step 2), the average particle size of the γ-alumina is 1 to 2 μm.
6. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The flame-retardant filler layer is composed of perlite, rock wool and silica aerogel mixed in a mass ratio of 1:0.4-0.6:0.2-0.
4.
7. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The decorative layer is a sliced veneer of catalpa or ash wood, with a thickness of 0.3 to 0.8 mm, and is treated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624 B1.
8. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The spacer layer is a three-layer plywood with a thickness of 3-8 mm, which is impregnated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624 B1.
9. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The frame layer is a solid poplar or pine wood frame with a thickness of 15-25mm, which is treated with phytic acid solution to achieve a flame retardant rating of not less than GB 8624B1.
10. The manufacturing process of the multi-layer composite wood fireproof door according to claim 1, characterized in that: The total thickness of the heat-insulating and flame-retardant layer is 40-50mm, wherein the thickness of the solid wood frame is the same as the thickness of the flame-retardant filling layer, and the total thickness of the flame-retardant coating is 2-4mm.
